SARS-CoV-2 vaccine breakthrough infection following a previous infection in a healthcare worker. Issue 3 (March 2022) - Gupta, Aayush; Bhoyar, Rahul; Mirza, Shahzad; Jolly, Bani; Senthivel, Vigneshwar; Shamnath, Afra; Divakar, Mohit Kumar; Imran, Mohamed; Gupta, Vishu; Agrawal, Srashti Jyoti; Mukhida, Sahjid; Sivasubbu, Sridhar; et al.
Highlights: Symptomatic SARS-CoV-2 infection post natural infection and 2 doses of ChAdOx1. Moderate levels of antibodies were detected 2 weeks post natural infection. Patient tested SARS-CoV-2 positive 30 days after the second dose of vaccine. Genomic analysis confirmed the infection with B.1.617.2 variant of SARS-CoV-2.